212 CHILDHOOD TOOTH DECAY PREVENTION: EDUCATING PARENTS IN MOSCOW, IDAHO. Issue 1 (1st January 2007) - Hansen, L.
Abstract : Purpose: Many parents are not aware that the first permanent molars, erupting around ages 5 to 7, are the most susceptible to tooth decay. Several interventions exist to prevent dental caries, and studies show that childhood tooth decay can be reduced through oral health education with parents. An education project was developed in Moscow, Idaho, to inform parents of prekindergarten children of measures for preventing childhood tooth decay. Methods: This project took place in several venues. First, the 5-year-old well-child electronic patient handout at Moscow Family Medicine was updated to include information about permanent tooth eruption and dental sealants. Second, a dental decay prevention booth was set up at the local farmers market with an informative poster, sealant brochures, fluoride handouts, and free children's toothbrushes. The booth was staffed by a local dental hygienist and a second-year medical student, and parents' knowledge of preventive measures was informally assessed. Third, the Moscow Head Start Program was given a poster on dental decay prevention and sealant and fluoride brochures for further education of the parents of prekindergarten children. Results: Caries prevention techniques were discussed with more than 100 parents at the farmers market and more than 120 sealant brochures and children's toothbrushes were distributed. Although many parents understood the importance of flossing, brushing, and fluoride, fewer knew about sealants, and none realized that permanent teeth appear in children as young as 5 years old. Numerous more parents now have access to tooth eruption and decay prevention information through the Moscow Family Medicine 5-year-old well-child electronic patient handouts and the Moscow Head Start Program. Conclusion: Parent education is critical to and effective in preventing childhood decay. Our assessment suggests that many parents lack a thorough understanding of the timing of permanent tooth eruption and of the measures available to prevent tooth decay. There is likely great potential for improvement in preventive dental care in children, and education programs like those described here may be an effective means to do so. In the future, formal studies should more rigorously assess parents' dental hygiene knowledge and determine the efficacy of specific interventions for providing childhood dental decay education.